The in vitro impact of toothpaste extracts on cell viability. (17th March 2015) - Cvikl, Barbara; Lussi, Adrian; Gruber, Reinhard
<x xml:space="preserve">Abstract</x> Toothpastes contain three main components: detergents, abrasives, and fluoride. Detergents, particularly sodium lauryl sulfate, have been proposed as components that enable toothpastes to produce cytotoxic effects in vitro. However, not all toothpastes contain sodium lauryl sulfate, and almost no studies have found an association between detergents and the in vitro cytotoxicity of toothpastes. The present study examined the in vitro cytotoxicity of nine commercially available toothpastes containing four different detergents. Toothpastes were diluted in serum‐free medium, centrifuged, and filter sterilized. The half‐lethal concentration of the toothpaste‐conditioned medium (TCM) was calculated based on the formation of formazan by gingival fibroblasts, oral squamous cell carcinoma HSC‐2 cells, and L929 cells. Cell proliferation was analyzed, and live‐dead staining was performed, after exposure of cells to conditioned medium prepared with 1% toothpaste (1% TCM). It was found that toothpastes containing sodium lauryl sulfate and amine fluoride strongly inhibited cell viability with the half‐lethal concentration being obtained with conditioned medium prepared with approximately 1% toothpaste (1% TCM). Toothpastes containing cocamidopropyl betaine and Steareth‐20 showed higher half‐lethal concentration values, with the half‐lethal concentration being obtained with conditioned medium prepared with 10% (10% TCM) and 70% (70% TCM) toothpaste, respectively. Proliferation and live–dead data were consistent with the cell‐viability analyses. These results demonstrate that the type of detergent in toothpastes can be associated with changes in in vitro cell toxicity.